Critique, social media and the information society - Sandoval, Marisol; Fuchs, Christian, 1976- (New York Routledge, 2014)
"Now more than ever, we need to understand social media - the good as well as the bad. We need critical knowledge that helps us to navigate the controversies and contradictions of this complex digital media landscape. Only then can we make informed judgments about what's happening in our media world, and why.
Keywords: Medios de comunicación social; Sociedad de la información